Video dubbing as a strategy for reducing foreign language speaking anxiety levels - Fuentealba Jiménez, Tamara (Universidad Estatal a Distancia, 2025)
The present action research attempts to describe the influence of the video dubbing process to reduce primary school students’ speaking anxiety levels in the English as a Foreign Language (EFL) classroom. The intervention consisted of 5 sessions where students worked in pairs practicing reading aloud the dialogue of a movie scene, using the video as an input for intralingual dubbing, to finally record and synchronize their voices with the scene. The participants of this study were 8 Chilean students from 8th grade who were selected based on their high levels of speaking anxiety in the EFL classroom. To analyze the effect of this strategy, a Likert scale, semi structured interviews, and observations were conducted. Findings revealed that the dubbing process contributed to decrease the participants’ speaking anxiety levels, declaring to feel more confident, less nervous, and more willing to participate in the EFL classroom, concluding that this strategy has proven to be effective for this purpose.